The information search process of U.P. Diliman undergraduate students on wiki sites Luz Mercedes H. Santos ; Grace Marie B. Gonzales, adviser ; Florenda D. Mallari, reader. - Santos, Luz Mercedes H.
This study, a descriptive type of research, is an in-depth look into the information seeking behavior of the undergraduate students in U.P. Diliman through various wiki sites based on Kuhlthau's (1993) Information Seeking Process (ISP) Model which makes use of six (6) stages with three (3) realms. This paper further assessed the level usage of students of wiki sites in their information requirement for their undergraduate studies. It offers primary information on the cognitive, affective and physical real experiences of the users of wiki sites as information sources was conducted.